The Origins of Radical Criminology, Volume III From Middle Ages to Renaissance - Georgoulas, Stratos (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
"In this important contribution, Stratos Georgoulas offers a comprehensive and in-depth exploration of the origins of critical criminology. Rarely do traditional textbooks cover this material in enough depth for readers to truly understand the historical developments of criminology. Georgoulas conveys his innovative review in a fascinating way that takes the reader into new realms rarely visited in criminology. Students and scholars alike will gain invaluable insights and engage with the rich history presented here." - Chad Posick, Associate Professor of Criminal Justice & Criminology, Georgia Southern University, USA "The Origins of Radical Criminology is a major work. In its three volumes published so far, Stratos Georgoulas conducts a genealogical tour de force against the criminological hegemony that shapes our worldview; a truly critical exercise that, by definition, can only achieve its goal from a radical approach. And so it does, to remind us that the history of resistance is as long and diverse as the history of the powers they must confront, and that the fight goes on." - Daniel Jiménez-Franco, Coordinator of the European Group for the Study of Deviance & Social Control, Universidad de Zaragoza, Spain This book critically explores the development of radical criminological thought through the social, political and cultural history of the Middle Ages to the Renaissance. It follows on from the previous volume which examined Classical Greece until the emergence of the early Christian movement in the Roman empire. Through separate chapters, it discusses the key literature (myths, fairy tales and Shakespeare), religions and philosophers of the era, and the development of early radical views and issues over time. This book examines the links between the origins of radical criminology and its future. It speaks to those interested in the (pre)history of criminology and the historical production of criminological knowledge, drawing on Criminology, Sociology, Classics, History, Philosophy, Ancient Literature and Politics. Stratos Georgoulas is Professor and Deputy Head of the Department of Sociology at the University of the Aegean, Greece. He is recognized in the scientific field of Critical Criminology, winning international awards for teaching in the USA (Fulbright), Canada, Slovakia, Syria, Jordan and Palestine.
1. Introduction -- 2. For a social history of the common medieval European area -- 3. Medieval philosophy -- 4. Byzantine Thought.-5. From Humanism to the dawn of new age -- 6. Utopias -- 7. Myths and fairy tales -- 8. Literature -- 9. A Dialogue with Historical Criminology.
Keywords: Criminology-History.; Critical criminology; Criminology; European literature-Renaissance, 1450-1600.; Philosophy, Medieval; Social history; History of Criminology; Critical Criminology; Criminology Theory; Early Modern and Renaissance Literature; Medieval Philosophy; Social History